Exosomal small RNA profiling in first-trimester maternal blood explores early molecular pathways of preterm preeclampsia - Gál, Luca; Fóthi, Ábel; Orosz, Gergő; Nagy, Sándor; Than, Nándor Gábor; Orbán, Tamás I. (Frontiers in Immunology, 2024)
Introduction:Preeclampsia (PE) is a severe obstetrical syndrome characterized by the new onset of hypertension and proteinuria and it is often associated with fetal intrauterine growth restriction (IUGR). PE leads to long-term health complications, therefore, the early diagnosis would be crucial for timely prevention. There are multiple etiologies and subtypes of PE, and this heterogeneity has inhibited accurate identification at a presymptomatic phase. Recent investigations pointed towards the potential roles of small regulatory RNAs in PE, and these species traveling in extracellular vesicles (EVs) in the circulation raised the possibility for non-invasive diagnostics. The aim of this study was to investigate the behavior of EV contained small regulatory RNAs in the most severe subtype of PE with IUGR.We isolated exosomal EVs from first trimester peripheral blood plasma samples of women who later developed preterm PE with IUGR (n=6) and gestational age-matched healthy controls (n=14). Small RNA content of EVs and their differential expression were determined by next generation sequencing and further validated by quantitative real-time PCR. We also applied the rigorous exceRpt bioinformatic pipeline for small RNA identification, followed by target verification and Gene Ontology analysis.Results:Overall, >2700 small RNAs were identified across all samples, and of interest, the majority belongs to the RNA interference (RNAi) pathways. Among the RNAi species, 16 differentially expressed microRNAs were upregulated in PE, whereas upregulated and downregulated members were equally found among the six identified Piwi-associated RNAs. Gene ontology analysis of predicted small RNA targets showed enrichment of genes in pathways related to immune processes involved in decidualization, placentation and embryo development, indicating that the dysregulation of the elicited small RNAs is connected to the impairment of immune pathways in preeclampsia development.Finally, the subsequent validation experiments revealed that hsa_piR_016658 piRNA is a promising biomarker candidate for preterm PE associated with IUGR.Discussion:Our stringently designed study on a homogeneous patient group unraveled small RNAs in circulating maternal exosomes which act on physiological pathways perturbed in preterm PE with IUGR. Therefore, our small RNA hits are not only suitable biomarker candidates, but the revealed biological pathways may further inform us on the complex pathology of this severe PE subtype.